What makes you beautiful? A multimodal discourse analysis of female beauty ideals in print advertisements in Singapore shopping centres - Ong, Fonda Zheng Jing (Nanyang Technological University, 2020)
Advertising is a powerful social discourse that taps into and reinforces women’s insecurities and fear of unattractiveness. In this study, advertisements were collected from shopping centres in Chinatown, Geylang Serai and Little India to examine the portrayals of women in public multimodal advertisements in Singapore, and to investigate prevailing attitudes among Singaporean women towards beauty constructs targeted at the different ethnicities in Singapore. Adopting a discourse analysis type of approach, similar to Fairclough’s (1989) framework, this study looks at the features the advertisers used to get women to create particular meanings when they view the advertisements, such as the choice of lexical items, language(s), colloquialisms, and images used. These features were analysed to see what techniques advertisers use to convince women to buy the product or service, and what ideologies seem to be exemplified by the advertisements. The findings revealed that all three areas exhibit a single standard female beauty ideal: the use of fair-skinned models, the portrayal of women as confident, youthful and flawless, which are unrealistic and hard to achieve ideals. While there were some differences in the prevailing attitudes of beauty constructs of women between the different age groups and ethnicities, the majority of the participants believe that beauty comes from within – confidence, how an individual presents herself, character, personality, and embracing one’s own uniqueness.